EFEKTIFITAS EKSTRAK DAUN SAMBILOTO (ANDROGRAPHIS PANICULATA NESS) DENGAN KLORAMFENIKOL TERHADAP PERTUMBUHAN BAKTERI SALMONELLA TYPHI SECARA IN VITRO - FAJAR MUHAMMAD NASUTION; MUHAMMAD JALALUDDIN ASSUYUTHI CHALIL; ANNISA .; MELVIANA LUBIS (LP2MTBM MAKARIOZ, 2019)
S. typhi is a stem bacteria, and gram-negative bacteria causes of typhid fever that until now became a health problem . Sambiloto (Andrographis paniculata Ness) is a potentially medicinal plants because it has antibiotic effect on bacteria. Objective: This study aims to determine the effectiveness of sambiloto’s leaf ectract on Salmonella typhi growth in vitro. Method: this research use experimental method. The technique used in measuring antibiotic activity is the method of disk diffusion. Result: The result showed that the sambiloto’s leaf extract (Andrographis paniculata Ness) with concentration of 80%, 40%, 20% and 10% yielded the mean of clear zone diameter ie 9.93 mm, 9.61 mm, 8.74 mm, and 7.49 mm. in this study showed that each concentration has different inhibitory power between the one with the other which obtained the value (p<0.05) but in the concentration ratio of 40% with 80% obtained value (p>0.05). Conclusion: Sambiloto’s leaf extract has an inhibitory power to the growth of Salmonella typhi bacteria and it can be seen in the result of the study. The higher the concentration of sambiloto’s leaf extract given, more higher the clear zone forme on the agar medium.